Analisis Efisiensi Biaya terhadap Keputusan Penggunaan Outsourcing Bidang Cleaning Service dan Catering pada PT Kuwera Jaya Jakarta - Masruroh, Masruroh; Fernanda, Ferry; Wibowo, Tony (Bina Nusantara University, 2014)
Bustle to serve customers make the company should focus more on its core business. Nowadays, PT Kuwera Jaya manages and employs its own cleaning service activities and also gives money for meal to employees in supporting activities. Conditions of supporting activities make PT Kuwera Jaya analyze the cost efficiency of supporting activities either self hiring or outsourcing. This study compared the use of relevant cost for self hiring and outsourcing, so that it could be analyzed which is more efficient alternative based on the most relevant low costs. Because the plan would still be done in the future, then to consider possible changes in the future, it was created three scenarios: pessimistic, moderate, optimistics with each of the relevant assumptions for each scenario. Results of the study indicate that the three scenarios using outsourcing as a viable alternative chosen by PT Kuwera Jaya because it could minimize the cost of supporting good cleaning service activities to manage the activities of cleanliness and also catering to provide lunch for employees. Suggestion in this research is PT Kuwera Jaya should immediately decide to use outsourcing in supporting the activities of cleaning service and catering. In addition to the benefits of outsourcing for cost efficiency, the field of activity is allowed in Employment Act No 13 2003, Articles 64 to 66.